Scale-model method for measuring noise reduction in residential buildings by vegetation. (April 2015) - Jang, Hyung Suk; Kim, Ho Jun; Jeon, Jin Yong
Abstract: This paper proposes an evaluation procedure using a scale model to assess the noise reduction effects of vegetated façades for sustainable urban building designs. The absorption coefficients of the scale-model materials were measured to fit the absorption characteristics of real vegetation. The ground impedance of asphalt was also measured to deduce the acoustical properties of ground surfaces and to select the ground material. To assess the reduction of road traffic noise, a line source for a 1:10 scale model was modelled using ribbon tweeters that generated high frequencies ranging from 1 kHz to 40 kHz. Accordingly, the effects of adding vegetated façades were evaluated in the scale model of a street canyon. The noise reduction due to the vegetated façades was less than 2 dB at pedestrian level in a two-lane street canyon. The scale model results were compared with geometric computer simulation results, and both evaluation methods showed similar results. The suggested modelling method can be useful for evaluating the noise reduction in street canyons by vegetation considering realistic features such as the absorption, scattering, and diffraction associated with the materials and sound sources according to the shape of the vegetation. Highlights: Scale-model vegetation materials with realistic absorption coefficients were used. The ground impedance was measured to select the asphalt scale model. A line source was constructed using a ribbon tweeter array. The insertion loss of vegetated façades in a two-lane street canyon was <2 dB.